Efficacy and safety of paliperidone palmitate 3-month versus 1-month formulation in patients with schizophrenia: comparison between European and non-European population - Savitz AJ (Dove Medical Press, 2019)
Adam J Savitz,1 Haiyan Xu,1 Srihari Gopal,1 Isaac Nuamah,1 Paulien Ravenstijn,2 David Hough,1 Ludger Hargarter3 1Janssen Research & Development, LLC, Raritan, NJ, USA; 2Janssen Research & Development, a Division of Janssen Pharmaceutica NV, Beerse, Belgium; 3Medical & Scientific Affairs, Janssen Cilag EMEA, Neuss, Germany Purpose: This randomized, double-blind (DB), non-inferiority phase 3 study was conducted to assess the efficacy and safety of paliperidone palmitate 3-month (PP3M) vs 1-month formulation (PP1M) in European and non-European patients with schizophrenia. Patients and methods: In this randomized, DB, parallel-group study, adult patients (18–70 years) with schizophrenia (per DSM-IV-TR) having Positive and Negative Syndrome Scale (PANSS) total score between 70 and 120; previously stabilized on PP1M were enrolled. The study had 4 phases: screening (3 weeks), open-label (OL) stabilization (17 weeks), DB (48 weeks) and follow-up (4–12 weeks) phase. Patients were treated with fixed-dose PP3M (175–525 mg eq deltoid/gluteal) or PP1M (50–150 mg eq deltoid/gluteal) for 48 weeks in DB phase. Results: In total, 487 European (PP3M, n=242; PP1M, n=245) and 508 non-European patients (PP3M, n=241; PP1M, n=267) entered DB phase (modified intent-to-treat (mITT) [DB] analysis set). Among the 508 non-European patients in mITT set, 67.7% were from Asia (n=344) and 32.3% were from rest of world (ROW, n=164). During the DB phase, similar percentage of Europeans (PP3M: 7%; PP1M: 8%) and non-Europeans (PP3M: 9%; PP1M: 10%) experienced relapse (Kaplan–Meier estimate PP3M–PP1M [95% CI] of percentage of relapse-free patients at the end of DB phase [primary endpoint]: European: 1.0% [-4.3%; 6.2%]; non-European: 1.4% [-4.4%; 7.1%]; Asian: 1.6% [-5.7%; 9.0%]; and ROW: 1.4% [-7.0%, 9.8%], per-protocol analysis set). Incidence of treatment-emergent adverse events (TEAEs) was lower in Europeans (PP3M: 56%, PP1M: 59%) than non-Europeans (PP3M: 80%, PP1M: 73%). The most commonly reported TEAE was weight gain. Conclusion: PP3M showed similar efficacy to PP1M in Europeans and non-Europeans, consistent with non-inferiority of PP3M to PP1M observed in overall population. Rates of AEs were higher in non-Europeans. However, weight gain was greater in non-Europeans, especially the Asian population. Keywords: long-acting injectable, non-inferiority, randomized, relapse, tolerability